Investors’ Overreaction on Stock Circuit Breakers and Signaling – A Research on Pakistan Stock Exchange: Investors’ Overreaction on Stock Circuit Breakers and Signaling – A Research on Pakistan Stock Exchange (KASBIT Business Journal, 2024)
Purpose – To investigate the effect of circuit breakers on investors' post-event investment behavior and potential overreaction.Design/methodology/approach - We analyzed daily stock returns (as the dependent variable) for instances when a circuit breaker was triggered, using the preceding day's returns as an independent variable. To enhance the study's robustness, we divided our sample into three distinct panels and conducted mean and variance equality tests for each. The sample consisted of firms from the KSE-100 index. We applied Ordinary Least Squares (OLS) regression analysis to these panels.Findings - The average return for stocks on the day following a circuit breaker event was found to be 6.20% (1.24 times the circuit breaker threshold). Returns typically followed the same direction (positive/negative) as the circuit breaker event. Notably, negative circuit breakers had less impact on investors compared to positive ones, aligning with prospect theory.Research limitations/implications - This study aids in understanding the impact of circuit breakers on investor overreaction, contributing to better-informed market decisions. The research is limited to circuit breaker events; future studies may employ different methodologies, statistical tools, timeframes, and markets.Originality/value - This research advances the understanding of behavioral finance, particularly in the context of market signaling and information asymmetry. It addresses the gap in literature on behavioral finance's role in stock market signaling by examining the effects of circuit breaker events on investor overreaction.
Keywords: Circuit Breakers; Signaling; Prospect Theory; Disposition Effect